Optimization of enzymatic hydrolysis of sugarcane bagasse for bioethanol production - Rahmath Abdulla; Nur Yenney Arsha; Mohd Khalizan Sabullah; Ahmad Asnawi Mus (Faculty of Science & Natural Resources, UMS, 2024)
Biofuels have emerged as a sustainable solution to the global energy crisis, especially amid declining fossil fuel reserves. Their continuous feedstock availability enhances engine efficiency and reduces greenhouse gas emissions. Lignocellulosic biomass, recognized as a valuable renewable resource, can be transformed into solid, liquid, and gaseous biofuels, meeting rising global energy demands. Various methods for biomass conversion have been developed, yet biofuel yields depend significantly on biomass composition and reaction conditions. Among these, agricultural lignocellulosic wastes, particularly sugarcane bagasse (SCB), have garnered attention as a viable alternative to fossil fuels. Sugarcane, predominantly cultivated in tropical and subtropical regions, is favored for bioethanol production due to its high biomass yield and fermentable sugar content. SCB is composed of approximately 50% cellulose, 25% hemicellulose, and 25% lignin, making it an ideal feedstock. However, efficiently releasing fermentable sugars from SCB remains a major challenge in bioethanol production. This study optimizes the enzymatic hydrolysis process to enhance sugar release from SCB. Initially, SCB underwent sulfuric acid pretreatment followed by enzymatic hydrolysis using cellulases and pectinases. The optimal hydrolysis conditions were determined to be 50°C at a shaking speed of 200 rpm over a 24-hour incubation period, achieving a high glucose concentration of 28.94 g/mL. This integrated approach of sulfuric acid pretreatment and enzymatic hydrolysis demonstrates significant potential for improving bioethanol production from SCB, contributing to the development of sustainable energy alternatives.